Engineering the Steroid Hydroxylating System from Cochliobolus lunatus in Mycolicibacterium smegmatis - Carmen Felpeto-Santero; Beatriz Galán; José Luis García (Microorganisms, 2021)
14α-hydroxylated steroids are starting materials for the synthesis of contraceptive and anti-inflammatory compounds in the steroid industry. A synthetic bacterial operon containing the cytochrome P450 CYP103168 and the reductase CPR64795 of the fungus Cochlioboluslunatus able to hydroxylate steroids has been engineered into a shuttle plasmid named pMVFAN. This plasmid was used to transform two mutants of Mycolicibacterium smegmatis named MS6039-5941 and MS6039 that accumulate 4-androstene-3,17-dione (AD), and 1,4-androstadiene-3,17-dione (ADD), respectively. The recombinant mutants MS6039-5941 (pMVFAN) and MS6039 (pMVFAN) were able to efficiently express the hydroxylating CYP system of C.lunatus and produced in high yields 14αOH-AD and 14αOH-ADD, respectively, directly from cholesterol and phytosterols in a single fermentation step. These results open a new avenue for producing at industrial scale these and other hydroxylated steroidal synthons by transforming with this synthetic operon other Mycolicibacterium strains currently used for the commercial production of steroidal synthons from phytosterols as feedstock.